Ethical concerns in contemporary virtual reality and frameworks for pursuing responsible use - Raja, Urooj S.; Al-Baghli, Reem (Frontiers in Virtual Reality, 2025)
Researchers have identified various ethical issues related to the use of VR. For example, issues of consent, privacy and harm. It is important to address these issues as VR impacts various industries, including communications, education and entertainment. Existing ethical frameworks in particular may be the closest tool we have when it comes to understanding how to curb some of the ethical challenges that the technology presents. Recent work names ethical concerns related to VR, such as privacy and accessibility; however, we note that less discuss frameworks that can be used to guide responsible VR use. Such work also glosses over what various audiences think about ethical issues. This information in turn could be used to determine which existing frameworks can provide guidance for responsible use. To address this gap, we examine current literature, government documents, and conduct an analysis of 300 Amazon reviews of three top-rated VR products—to see whether and what ethical concerns various audiences identify. That is, we ask two questions: 1) Are three specific types of audiences naming ethical VR issues, and if so, what are the issues? 2) What frameworks could potentially guide users toward responsible use? We find that users are concerned about ethical issues and that three frameworks could guide us towards more responsible VR use: 1) Institutional Review Board (IRB) frameworks, 2) a care ethics framework, and 3) co-created, living ethical codes. We further pull from these three frameworks to offer a new ethical synthesis framework or ESF framework that could guide responsible use.